2021
DOI: 10.1103/physrevc.103.025811
|View full text |Cite
|
Sign up to set email alerts
|

Mass measurements of neutron-rich indium isotopes for r -process studies

Abstract: A new series of neutron-rich indium mass measurements are reported from the TITAN multiplereflection time-of-flight mass spectrometer (MR-TOF-MS). These mass measurements cover 125−134 In (N = 76 − 85) and include ground states as well as isomeric states. The masses of nuclei in this region are known to be of great importance for accurately modeling r-process nucleosynthesis, and the significance of the reported neutron-rich indium masses is discussed in this context. Results are compared with earlier experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 57 publications
2
12
1
Order By: Relevance
“…Version available at http://www.nndc.bnl.gov/ensarchivals/ accessed on 17 September 2020) [6]. Measurements of isomers and their properties continue to be a point of experimental interest for a variety of reasons, including not only as astrophysical model inputs, but also for applications in industry, medicine, and tests of fundamental nuclear physics [7][8][9][10][11][12][13][14][15][16][17]. For a recent review, see [18].…”
Section: Introductionmentioning
confidence: 99%
“…Version available at http://www.nndc.bnl.gov/ensarchivals/ accessed on 17 September 2020) [6]. Measurements of isomers and their properties continue to be a point of experimental interest for a variety of reasons, including not only as astrophysical model inputs, but also for applications in industry, medicine, and tests of fundamental nuclear physics [7][8][9][10][11][12][13][14][15][16][17]. For a recent review, see [18].…”
Section: Introductionmentioning
confidence: 99%
“…Detailed review of the available data sources showed that neither of the two reaction studies [106,107] which observed the higher-lying candidate level could assign it an unambiguous spin-parity or provide conclusive arguments for its identification as the IAS. The lower-lying candidate level was first observed in 58 Ni( 16 O, 14 C) 60 Zn reactions [108] and suggested as the IAS, based on the agreement of the observed excitation energy with a CDE prediction for E x ( 60 Zn i ). The same level was later observed as a cascade of βdelayed gamma rays in βγ-spectroscopy studies by Mazzocchi et.al [69] and Orrigo et al [70], which both identified it as the T = 1 IAS.…”
Section: A Location Of the Proton Drip Line At Z = 31mentioning
confidence: 76%
“…Providing mass separation powers of several 100 000 and background suppression factors as high as 10 4 [54], massselective retrapping allows one to leverage the characteristics of the isotope-separation on-line (ISOL) method, namely high rare isotope production yields at the expense of heavy isobaric contamination. After the first utilization in [56], the technique has been successfully used in several other on-line measurements at TITAN [57,58].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While this work was being completed, the 133 In mass was measured [33]. The next most informative measurement depends on the most likely r-process scenario, though clearly the (Z = 50,N = 82) region of the periodic table is a source of many informative mass measurements.…”
Section: Information Gain Relative To R-process Abundancesmentioning
confidence: 99%